Optimalisasi Media Digital untuk Mendukung Pembelajaran Mendalam pada Fase Fondasi - Nurhopipah, Siti; Fauziyah, Nurul Hikmah; Ulfatullailah, Eneng; Sari, Rika Widia (TSAQOFAH, 2026)
Although the use of digital media in early childhood education (PAUD) institutions and primary schools at the Fase Fondasi has been fairly adaptive, its utilization to support deep learning remains suboptimal. This study aimed to analyze the optimization of digital media to support deep learning at the Fase Fondasi through literature review and observations in kindergartens and primary schools. The findings indicate that effective use of digital media is characterized by interactive, play-based learning designs that are mindful, meaningful, and joyful, and that are integrated with the learning outcomes of the Fase Fondasi. Implementing these strategies has a significant impact on increasing learner engagement, strengthening understanding of basic concepts, and stimulating the early development of higher-order thinking skills, including problem-solving and basic reasoning in young children. The study recommends teacher training and strengthened parent–school partnerships as prerequisites for the holistic implementation of digital media optimization to support deep learning at the Fase Fondasi.